KIT, DEVICE, AND METHOD FOR DETECTING OVARIAN TUMOR - SUDO HIROKO; KOZONO SATOKO; KAWAUCHI JUNPEI; KIDA YUHO; KONDOU SATOSHI; NOBUMASA HITOSHI; KATO TOMOYASU; OCHIYA TAKAHIRO (2019)
The present invention provides: a kit or device for detecting an ovarian tumor, the kit or device including a nucleic acid for detecting miRNA in a specimen from a subject; and a method for detectingan ovarian tumor, the method including the measurement of this miRNA in vitro. 本申请提供包含用于检测受检体的样本中的miRNA的核酸的卵巢肿瘤检测用试剂盒或装置、以及包括体外(in vitro)测定该miRNA的步骤的检测卵巢肿瘤的方法。